Analisis Determinan Pemanfaatan Pelayanan Kesehatan Gigi dan Mulut di Kota Depok pada Masa Pandemi Covid-19 - Kurnia Permitasari; Herry Novrinda; Risqa Rina Darwita; Armasastra Bahar (Andalas Dental Journal, 2023)
During the Covid-19 pandemic, starting from 2019, there was a 62.78% gap in dental and oral care patient visits at the Depok City Health Center. Data from the Depok City Health Department indicates a decrease in patient visits at the Depok City Health Center in 2018 by 90,366, in 2019 by 90,979, in 2020 by 33,861, and in 2021 by 29,455. The purpose of this study is to determine the factors associated with the utilization and selection of dental and oral healthcare providers in Depok City during the Covid-19 pandemic. It is a cross-sectional study conducted on the population of Depok City in 2021, with respondents who are willing to fill out online questionnaires, understand the Indonesian language, are able to read, write, communicate, and have a smartphone. The sample size is 580 people, and multivariate analysis with multinomial regression is used. The research results show that during the Covid-19 pandemic, 26.7% of the population utilized government services, 11.6% utilized private services, and 61.7% did not utilize any services. The multivariate analysis results indicate that age, marital status, medical history, insurance, and perception of needs have a significant relationship with the prediction of choosing to utilize dental and oral health examinations provided by the government and private sectors. The determinant factors associated with the utilization of dental and oral health services during the Covid-19 pandemic are age, having a medical history, having insurance, and having a perception of needs.